Some Problems and Opportunities of Distance Learning (Journal of Educational Sciences, 2020)
In today’s world of information development, the importance of distance education is growing. Its main feature is that it allows to obtain the necessary knowledge using modern educational informa¬tion and digital educational resources in distance. For a high-quality organization, there must be an educational platform, communication channels, digital educational resources. In the context of distance learning, communication with a student occurs through information and communication means, and, accordingly, a sufficiently high level of knowledge of digital, information and methodological resources is required from the teacher. The methodological foundations of the study are systemic, activity-based, synergetic approaches; methods of analysis, experiment, generalization and comparison of experimental results are also used. The theoretical and practical significance of the study is the clarification of the concepts of distance education, a methodological analysis of the available educational resources, the study of the level of teachers’ readiness to work with digital resources and the ways of their development. Interim results were obtained and an analysis of the effectiveness of available educational platforms and digital resources in the process of distance learning of educational organizations was carried out. The assessment of changes in the digital competency of College teachers for April and September 2020 (the beginning of mass distance education in Kazakhstan due to the introduction of the COVID-19 quarantine in April 2020 and the current state of the beginning of the 2020/2021 academic year) was carried out. 52 teachers of Zh. Dosmukhamedov Higher Pedagogical College of the West Kazakhstan region took part in the research.  This research is an interim one, and further work will continue on the use of effective digital resources and the development of distance learning methods. Key words: distance education, digital resources, digital literacy of teachers, learning platforms.